Analysis on the influence factors of Bitcoin's price based on VEC model - Yechen Zhu; David Dickinson; Jianjun Li (Financial Innovation, 2017)
Background: Bitcoin, the most innovate digital currency as of now, created since 2008, even through experienced its ups and downs, still keeps drawing attentions to all parts of society. It relies on peer-to-peer network, achieved decentralization, anonymous and transparent. As the most representative digital currency, people curious to study how Bitcoin' price changes in the past. Methods: In this paper, we use monthly data from 2011 to 2016 to build a VEC model to exam how economic factors such as Custom price index, US dollar index, Dow jones industry average, Federal Funds Rate and gold price influence Bitcoin price. Result: From empirical analysis we find that all these variables do have a long-term influence. US dollar index is the biggest influence on Bitcoin price while gold price influence the least. Conclusion:From our result, we conclude that for now Bitcoin can be treated as a speculative asset, however, it is far from being a proper credit currency.
Keywords: 650; Bitcoin price; Gold price; US dollar index; VEC model